The social shaping of a diagnosis in Next Generation Sequencing. Issue 4 (2nd October 2021) - Kuiper, Janneke M.L.; Borry, Pascal; Vears, Danya F.; Van Hoyweghen, Ine
Abstract : Although Next Generation Sequencing (NGS) has increased our ability to test and diagnose, its results are often not clear-cut and require a complex interpretation and negotiation process by both healthcare professionals and patients involved. In this paper, we explore how diagnoses identified through NGS are socially shaped under influence of the broader social context. Using an analytical framework stemming from the sociology of health and illness and science and technology studies, with a focus on the construction of diagnosis and the role of uncertainty in medicine, we analyze the existing corpus of literature on NGS diagnostic practices. We show how in this early implementation phase of NGS, in which standardization efforts are not yet solidified, the boundary struggles around diagnoses obtained through NGS are particularly visible. We discuss the different steps in the diagnosis shaping process and what it subsequently entails to give and a receive a diagnosis using NGS.